Nilai-nilai Sosial Pendidikan Tradisi Mantu Bubak dalam Pernikahan Adat Jawa di Desa Gunungan - Ferrian Bima Cahyono Putro; Muhammad Hanif (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
Mantu Bubak in Javanese traditional marriage is one of the traditions that has been preserved from generation to generation in Gunungan Village, Kartoharjo District, Magetan Regency. The purpose of this study was to determine the social values of education in the Mantu Bubak tradition in Javanese traditional marriages in Gunungan Village. The type of research used is descriptive qualitative research. Qualitative methods are social research steps to obtain descriptive data in the form of words and pictures. This research was conducted using descriptive research methods in the people of Gunungan Village. From the research conducted, the results obtained are as follows: (1). There is a value of mutual cooperation in the Mantu Bubak tradition in Javanese traditional weddings in Gunungan Village, (2). There is a religious value in the Mantu Bubak tradition in Javanese traditional weddings in Gunungan Village